RekonstRuksi HistoRiogRafi islamisasi dan Penggalian nilai-nilai ajaRan sunan kalijaga - Hak, Nurul (Universitas Islam Negeri Raden Intan Lampung, 2016)
This article examines the Islamization and the Islamic values, in the context of the spread of Islam through the case of Sunan Kalijaga. In relation to the Islamization by Sunan Kalijaga, the author considers it is necessary to reconstruct his Islamization, not only within the scope of Java, but also related to regional and even international connections. The word “regional” in this context is the archipelago as the “scope” of Islamization through the maritime route in 15th and 16th century. The international connection is the relationships and networks that occurred during these centuries. To elaborate this material, I use the context and diffusion of culture as a theoretical framework. Theories related to the “context” related to the socio-economic and political conditions in the archipelago in these centuries. The cultural diffusion theory used to explain the Islamization of West Java and Central Java, the major places where Sunan Kalijaga spread Islam. The approach applied in this research is biography, history, and socio-cultural. The results show that although the major spot of Sunan Kalijaga’s Islamization was in Java land, the center of the Islamization process actually located in Aceh through the kingdom of Samudera Pasai and the Islamic kingdom of Aceh Darussalam. In addition, the process of dissemination of Islam conducted by Sunan Kalijaga has produced “the vernacularized Islam” in the archipelago, more specifically in Java, which is characterized by convergence, assimilation, acculturation and syncretism between Islam and local culture.